2017
DOI: 10.1136/rmdopen-2016-000352
|View full text |Cite
|
Sign up to set email alerts
|

No impact of concomitant methotrexate use on serious adverse event and serious infection risk in patients with rheumatoid arthritis treated with bDMARDs: a systematic literature review and meta-analysis

Abstract: ObjectivesTo compare the risk of serious adverse events, serious infections and death caused by methotrexate and biological disease-modifying antirheumatic drug (bDMARD) combination therapy versus a bDMARD prescribed as monotherapy in rheumatoid arthritis (RA).MethodsA systematic literature review was conducted until February 2016 in PubMed, Embase and Cochrane Library databases by selecting randomised controlled trials comparing methotrexate and bDMARD combination therapy to bDMARD monotherapy in RA. The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…32 Due to a potential immunosuppressive effect, MTX and GCs may lead to a possible increase in infection risk, particularly in a susceptible population 33,34 ; as such, it is important to investigate their use concomitantly with bDMARDs. A systematic literature review and metaanalysis of randomized controlled trials demonstrated that combination therapy with bDMARDs and MTX did not increase the risk of serious infections vs bDMARD monotherapy, 35 in line with the results observed in this analysis (Supplementary Figures 5 and 6, available with the online version of this article). In addition, a systematic literature review of 88 studies showed that long-term (≥ 2 yrs) use of MTX monotherapy was not a risk factor for serious infections, including HZ.…”
Section: Discussionsupporting
confidence: 89%
“…32 Due to a potential immunosuppressive effect, MTX and GCs may lead to a possible increase in infection risk, particularly in a susceptible population 33,34 ; as such, it is important to investigate their use concomitantly with bDMARDs. A systematic literature review and metaanalysis of randomized controlled trials demonstrated that combination therapy with bDMARDs and MTX did not increase the risk of serious infections vs bDMARD monotherapy, 35 in line with the results observed in this analysis (Supplementary Figures 5 and 6, available with the online version of this article). In addition, a systematic literature review of 88 studies showed that long-term (≥ 2 yrs) use of MTX monotherapy was not a risk factor for serious infections, including HZ.…”
Section: Discussionsupporting
confidence: 89%
“…MTX has been found to be safe and efficacious in pediatric uveitis,[ 6 ] but interestingly few authors have noted that as compared with non-JIA children, JIA children on MTX without TNF inhibitors had a significantly increased tuberculosis infection rate. [ 7 8 ] Our patient had no other signs of systemic immunosuppression or of systemic TB. In our case, the SR abscess responded well to ATT and completely resolved with no recurrences till the follow-up period.…”
Section: Discussionmentioning
confidence: 88%
“…csDMARDs and the Risk of Infection in Patients with RA Evidence suggests that csDMARDs, such as methotrexate, confer no increased risk for SI or SI-associated mortality in patients with RA [107]. Indeed, the addition of methotrexate to a bDMARD regimen did not increase the risk of SI compared with bDMARD monotherapy in a meta-analysis of patients with RA [119]. These conclusions, however, differ from those from a Japanese cohort study, which identified the use of methotrexate as a risk factor for Pneumocystis pneumonia, although methotrexate use was negatively associated with the incidence of all infections [93].…”
Section: Treatment Regimens and The Risk Of Infection In Patients With Ramentioning
confidence: 99%